Effect of Tissue Inhomogeneity in Soft Tissue Sarcomas: From Real Cases to Numerical and Experimental Models. (25th July 2018) - Campana, Luca Giovanni; Bullo, Marco; Di Barba, Paolo; Dughiero, Fabrizio; Forzan, Michele; Mognaschi, Maria Evelina; Sgarbossa, Paolo; Tosi, Anna Lisa; Bernardis, Alessia; Sieni, Elisabetta
Electrochemotherapy is an established treatment option for patients with superficially metastatic tumors, mainly malignant melanoma and breast cancer. Based on preliminary experiences, electrochemotherapy has the potential to be translated in the treatment of larger and deeper neoplasms, such as soft tissue sarcomas. However, soft tissue sarcomas are characterized by tissue inhomogeneity and, consequently, by variable electrical characteristic of tumor tissue. The inhomogeneity in conductivity represents the cause of local variations in the electric field intensity. Crucially, this fact may hamper the achievement of the electroporation threshold during the electrochemotherapy procedure. In order to evaluate the effect of tissue inhomogeneity on the electric field distribution, we first performed ex vivo analysis of some clinical cases to quantify the inhomogeneity area. Subsequently, we performed some simulations where the electric field intensity was evaluated by means of finite element analysis. The results of the simulation models are finally compared to an experimental model based on potato and tissue mimic materials. Tissue mimic materials are materials where the conductivity can be suitably designed. The coupling of computation and experimental results could be helpful to show the effect of the inhomogeneity in terms of variation in electric field distribution and characteristics.